THE COMPARATIVE PERFORMANCE BETWEEN FULL FUNCTIONAL AND SUBSET FUNCTIONAL JOB ROTATION OF RADIOLOGIC TECHNOLOGIST IN DIAGNOSTIC RADIOLOGY DEPARTMENT AT THE FACULTY OF MEDICINE, RAMATHIBODI HOSPITAL - ทิมาสาร ปวริศร; ชินะโชติ ภาวิน; ชาญกิจ ภูริพัฒน์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
The purposes of this research were to: 1) study about the formats of job rotation in radiologic technologist and 2) compare the performance between full functional and subset functional Job rotation of radiologic technologists. The research population was the radiologic technologists in Diagnostic Radiology Department at the Faculty of Medicine, Ramathibodi Hospiatal. The selected samples were the 9 experts of radiologic technologists in the research group. The data were collected by using the Delphi Technique. The research findings were as follows: 1) The format of subset functional job rotation in radiologic technologists were that the high experienced radiologic technologist must be working in his own room; the medium experienced radiologic technologists must be rotated in some rooms that had the same works; and the low experienced or newbie radiologic technologists must be rotated in all rooms. 2) The subset functional job rotation was more efficient than the full functional job rotation in all 5 areas: (1) general management, (2) expertise to use diagnostic radiological machine, (3) the service of patients, (4) the communication and coordination, and (5) the satisfaction of radiologic technologist in the job rotation.